The Cypriniformes Tree of Confusion - Britz, Ralf; Conway, Kevin W. (Zootaxa, 2011)
In a recent paper, Mooi & Gill (2010) raised various issues related to recent developments in molecular systematic ichthyology that they found alarming. They went so far as to call this a “crisis in fish systematics.” They criticised the trend that alternative trees for the placement of a taxon in question are not critically discussed and the reason for the divergent positions is not adequately evaluated. They raise the important question “On what basis is one topology to be preferred over the other?”